Microdialysis for chronic exertional compartment syndrome: a pilot study - Heinz Lohrer; Jochen Klein; Tanja Nauck; Tobias Schönberg (BMC, 2021)
Abstract Background Diagnosing chronic exertional compartment syndrome (CECS) is still a challenge. An increase in intramuscular pressure during and following exercise is accepted as the diagnostic standard. However, neither the methods used nor the interpretation of the obtained results are sufficiently standardized. Methods In the present pilot study, the metabolic state of CECS patients was investigated using microdialysis. We hypothesized that there was no difference in intramuscular concentrations of glucose, lactate, glutamate, and glycerol before and after exercise (H10) or between patients suffering from CECS and healthy control subjects (H20). This study was designed as an explorative case-control study (level of evidence III). Twelve patients suffering from CECS of the lower leg and six matched asymptomatic control subjects underwent microdialysis in the anterior (n = 7) or deep posterior compartment (n = 11) of the leg. Following ultrasound-guided insertion of the microdialysis catheters, 10-minute fractions of the dialysates were collected first during rest and then following fatigue- or pain-induced discontinuation of exercise. Dialysates were analysed for lactate, glucose, glutamate, and glycerol concentrations 6 × 10 min before and 6 × 10 min after exercise. Results Exercise-induced increases in lactate, glutamate, and glycerol concentrations were detected in both CECS patients and control subjects (all p < 0.001). No differences between CECS patients and control subjects were found by comparing the intramuscular glucose, lactate, glutamate, and glycerol concentrations at rest and following exercise (all p > 0.05). Conclusions We found exercise-induced increases in the lactate, glutamate, and glycerol levels in skeletal muscle. However, the metabolic changes did not differentiate CECS patients from healthy subjects. Trial registration The registration trial number is DRKS00021589 on DRKS. 'Retrospectively registered'. Date of registration: April 4, 2020.